Incorporating automation in a cytogenetics laboratory: three practitioners’ perspectives on benefits and limitations - Cecelia Miller; Jennie Thurston; Ninette Cohen (Molecular Cytogenetics)
Abstract Automation has been developed and continues to be refined for cytogenetics, including advances in the processing of samples, in analysis of conventional chromosome and fluorescence in situ hybridization (FISH) testing, and with artificial intelligence. Here we provide an overview of the various types of automation available to the cytogenetics laboratory and discuss possible benefits and limitations you may encounter based upon our collective experiences.